2011
DOI: 10.5194/hess-15-197-2011
|View full text |Cite
|
Sign up to set email alerts
|

Distributed specific sediment yield estimations in Japan attributed to extreme-rainfall-induced slope failures under a changing climate

Abstract: Abstract. The objective of this study was to estimate the potential sediment yield distribution in Japan attributed to extreme-rainfall-induced slope failures in the future. For this purpose, a regression relationship between the slope failure probability and the subsequent sediment yield was developed by using sediment yield observations from 59 dams throughout Japan. The slope failure probability accounts for the effects of topography (as relief energy), geology and hydroclimate variations (hydraulic gradien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…If the degree of compaction was relatively small between embankment fill materials, then the interface between the upper and lower portions may have lost the strength required to hold back the force of the reservoir water acting from the upstream side, leading to the first failure, which likely occurred in the upper portion of the dam. The damage may have been exacerbated by upstream slope slides that frequently occur because of saturation in artificially reclaimed soft alluvial slopes (Kawagoe et al, 2010;Ono et al, 2011a) when reservoirs are at full capacity (Sherard et al, 1963). The absence of transfer cracks in the other four dams investigated suggests that the major cause of failure was likely not deformation.…”
Section: Potential Breach Resulting From Cracks and A Slope Failurementioning
confidence: 99%
“…If the degree of compaction was relatively small between embankment fill materials, then the interface between the upper and lower portions may have lost the strength required to hold back the force of the reservoir water acting from the upstream side, leading to the first failure, which likely occurred in the upper portion of the dam. The damage may have been exacerbated by upstream slope slides that frequently occur because of saturation in artificially reclaimed soft alluvial slopes (Kawagoe et al, 2010;Ono et al, 2011a) when reservoirs are at full capacity (Sherard et al, 1963). The absence of transfer cracks in the other four dams investigated suggests that the major cause of failure was likely not deformation.…”
Section: Potential Breach Resulting From Cracks and A Slope Failurementioning
confidence: 99%
“…Furthermore, the Department of Water Resources [50] showed an increasing trend in soil moisture in northern Thailand. Both increasing rainfall and soil moisture are conducive for landslides [51]. A study by Petley [4] has found evidences for an increasing trend in fatal landslides in Asia.…”
Section: Local People's Perceptions Of Floodingmentioning
confidence: 99%
“…There are several recent studies on the sediment delivery from landslides, their contribution to the sediment flux, and erosion of the displaced toe (see for example Mackey and Roering, 2011;Schwab et al, 2008;Bayer and Linneman, 2011;Ono et al, 2011). In general, sediment discharge can be divided into stream channel sediment transport (bed load, suspended load, and wash load) and land surface transport (mass movement) (Mouri et al, 2011).…”
Section: Impact On Water Qualitymentioning
confidence: 99%